AN ANALYSIS OF ILLOCUTIONARY ACT IN THE MAIN CHARACTERS' UTTERANCES IN A MAN CALLED OTTO MOVIE - Nadiya, Nadiya Nadiya; Rohimajaya, Nur Azmi; Novari, Ari Fajria (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2025)
The purpose of this study was to examine the many forms of illocutionary acts and identify which ones were most frequently used in the main characters' utterances in the film A Man Called Otto. The study employed a qualitative method and involved content or document analysis. The researcher employed Austin and Searle's theories to answer the research questions. The researcher collected data on the script and film of A Man Called Otto through observation, documentation, and observation checklist procedures. The researcher employed three data analysis techniques: data reduction, data display, and conclusion. The results revealed that all forms of illocutionary acts were present in the utterances of all of the key characters in the film A Man Called Otto, including representative, directive, commissive, expressive, and declarative. Subject A (Otto) had 260 utterances, subject B had 100 utterances, and subject C (Sonya) had 31 utterances, all of which featured illocutionary behaviors. Representative is the most common type of illocutionary act in the main characters' utterances in the film A Man Called Otto, with 173 instances, followed by directive (126), expressive (55), declarative (24), and commissive (13). It may be inferred that there are several forms of illocutionary acts, with the representative act appearing most frequently in the major characters of the film A Man Called Otto.